Polydopamine nanotube mediated fluorescent biosensor for Hg(ii) determination through exonuclease III-assisted signal amplification. Issue 11 (11th May 2018) - A, Ravikumar; P, Panneerselvam
Abstract : We describe a highly sensitive fluorescence biosensor incorporating polydopamine nanotubes (PDNTs) based on the mechanism of exonuclease III (Exo III) assisted signal amplification for the determination of Hg 2+ in aqueous solution. Abstract : We describe a highly sensitive fluorescence biosensor incorporating polydopamine nanotubes (PDNTs) based on the mechanism of exonuclease III (Exo III) assisted signal amplification for the determination of Hg 2+ in aqueous solution. Fluorescent probes of FAM labeled ssDNA (FAM-ssDNA) adsorbed on the PDNTs act as an efficient quencher. In the presence of Hg 2+, the FAM-ssDNA can bind to Hg 2+ to form double stranded DNA (dsDNA) via the formation of T–Hg 2+ –T base pairs. Then, the dsDNA was removed from the surface of the PDNTs to restore the fluorescence. The release of the dsDNA was triggered by Exo III digestion. At the same time, the liberated Hg 2+ mediates a new cycle of digestion. This assay is ultrasensitive for the selective recognition of Hg 2+, and a detection limit as low as 10 pM was achieved. In addition, the fluorescent biosensing system also displays remarkable specificity to Hg 2+ in the presence of other possible competing ions. This approach was applied to the determination of Hg 2+ in real water samples with good recovery and high efficiency for practical analysis.